PAMP (Pathogen-associated molecular pattern)-induced changes in plasma membrane compartmentalization reveal novel components of plant immunity - Keinath, Nana (The journal of biological chemistry, 2010)
Plasma membrane compartmentalization spatiotemporally regulates cell-autonomous immune signaling in animal cells. To elucidate immediate early protein dynamics at the plant plasma membrane in response to the bacterial pathogen-associated molecular pattern (PAMP) flagellin (flg22) we employed quantitative mass spectrometric analysis on detergent-resistant membranes (DRMs) of Arabidopsis thaliana suspension cells. This approach revealed rapid and profound changes in DRM protein composition following PAMP treatment, prominently affecting proton ATPases and receptor-like kinases, including the flagellin receptor FLS2. We employed reverse genetics to address a potential contribution of a subset of these proteins in flg22-triggered cellular responses. Mutants of three candidates (DET3, AHA1, FER) exhibited a conspicuous defect in the PAMP-triggered accumulation of reactive oxygen species. In addition, these mutants showed altered mitogen-activated protein kinase (MAPK) activation, a defect in PAMP-triggered stomatal closure as well as altered bacterial infection phenotypes, which revealed three novel players in elicitor-dependent oxidative burst control and innate immunity. Our data provide evidence for dynamic elicitor-induced changes in the membrane compartmentalization of PAMP signaling components.